KAJIAN PENGISIAN DAN PENGEMBANGAN JABATAN FUNGSIONAL LINGKUP PEMERINTAH PROVINSI SULAWESI TENGGARA - Malesa, Malesa (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to examine filling and development as well as factors causing a decline in interest in joining functional positions within the scope of the Southeast Sulawesi Provincial Government in supporting the successful implementation of bureaucratic reform. This study is a type of qualitative and quantitative descriptive research on 24 employees of the Regional Civil Service Agency and functional officials of the Provincial Government and 60 employees of BKPSDM and functional officials of the City/Regency Government in Southeast Sulawesi. The results of the study show that: 1) The level of achievement according to the criteria for job analysis (task description instrument and job requirements) for Pemprov employees has been carried out with procedures compared to the Municipal Government and the Regency Government. This analysis is important because it forms the basis and reference for the formation of each position; 2). Workload analysis (comparing weight/workload with time norms and work volume). The Provincial Government is still very high compared to the Municipal Government and the Regency Government; 3) The first appointment to the Provincial Government branch has been carried out in accordance with the procedure, both in assessing the determination of credit scores, final rank/class decisions, STTPLP/functional training and education certificates, as well as DP3, etc., compared to the City Government and Regency Government; 4). The appointment of transfers from other positions of the Provincial Government has been carried out in a better procedure compared to the City Government and the Regency Government; 5) Appointments through inpassing/adjustments to functional positions have been carried out with procedures for both the Provincial Government and the City and Regency Governments. Adjustments need a competency test if not then the process will not be adjusted/inpassing; 6). Evaluation of work performance in the provincial government employees is carried out in accordance with the provisions compared to the City Government and Regency Government; 7) Competence improvement has been carried out in a balanced manner by both the Provincial Government and the City Government and Regency Government because it is realized that it is an important need for organizations to increase knowledge, skills and attitudes as well as increase job satisfaction and performance , as well as mobilizing employees; 8). The decline in employee interest in following jf is caused by factors of not having power, narrow duties and authority; educational qualifications have not been met; lack of socialization; the absence of clear incentive standards; and the process of increasing the class is quite long.